2021
DOI: 10.1101/2021.03.26.437180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The RNA sensor MDA5 detects SARS-CoV-2 infection

Abstract: Human cells respond to infection by SARS-CoV-2, the virus that causes COVID-19, by producing cytokines including type I and III interferons (IFNs) and proinflammatory factors such as IL6 and TNF. IFNs can limit SARS-CoV-2 replication but cytokine imbalance contributes to severe COVID-19. We studied how cells detect SARS-CoV-2 infection. We report that the cytosolic RNA sensor MDA5 was required for type I and III IFN induction in the lung cancer cell line Calu-3 upon SARS-CoV-2 infection. Type I and III IFN ind… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…For most viruses, the gene expression inductor for IFN a/b is dsRNA. Many viruses generated strategies that prevent dsRNA exposure in the cytoplasm (167)(168)(169). In reoviruses, dsRNA remains inside the capsid during the whole viral cycle.…”
Section: Viral Strategies Against Ifnsmentioning
confidence: 99%
“…For most viruses, the gene expression inductor for IFN a/b is dsRNA. Many viruses generated strategies that prevent dsRNA exposure in the cytoplasm (167)(168)(169). In reoviruses, dsRNA remains inside the capsid during the whole viral cycle.…”
Section: Viral Strategies Against Ifnsmentioning
confidence: 99%
“…Multiple studies reported that the RLR pathway is activated during SARS-CoV-2 infection for anti-viral responses in vitro (Kouwaki et al, 2021;Sampaio et al, 2021;Thorne et al, 2021;Wu et al, 2021;Yamada et al, 2021;Yin et al, 2021). For example, Thorne et al (2021) have reported that RNA sensing of SARS-CoV-2 in lung epithelium can contribute to robust macrophage activation, cytokine production and tissue inflammation.…”
Section: Sars-cov-2 Recognition By Rig-i-like Receptors (Rlrs) and To...mentioning
confidence: 99%
“…For example, Thorne et al (2021) have reported that RNA sensing of SARS-CoV-2 in lung epithelium can contribute to robust macrophage activation, cytokine production and tissue inflammation. Meanwhile, both Yin and Sampaio et al reported that SARS-CoV-2 is sensed by MDA5, NOD1, and LGP2, but not RIG-I and MAVS; while IRF3, IRF5, and NF-κB/p65 act as the major mediators of IFN response induction (Sampaio et al, 2021;Yin et al, 2021).…”
Section: Sars-cov-2 Recognition By Rig-i-like Receptors (Rlrs) and To...mentioning
confidence: 99%
“…Innate immune responses are initiated by recognizing viral PAMPs via PRRs [100] . Cytosolic RLRs including RIG-I, and MDA5, and endosomal TLRs mainly TLR-3, TLR-7, and TLR-8 are major PRRs responsible for detecting RNA virus infections such as coronaviruses and promoting the antiviral IFN pathway [101] , [102] , [103] , [104] . Ligand binding results in triggering the downstream adaptor proteins including myeloid differentiation primary response gene 88 (MyD88) and mitochondrial antiviral signaling protein (MAVS).…”
Section: Immunoediting In Sars-cov-2mentioning
confidence: 99%